THE RECENT PUBLIC DEFICITS AND THE ANALYTICAL DEFLECTIONS OF FISCAL SUSTAINABILITY COMPONENTS IN THE EU - Özker, Ahmet Niyazi (International Journal of Research -GRANTHAALAYAH, 2022)
This study is aimed to deal with the equivalence through fiscal deviations of the effect values of public deficits on fiscal sustainability as an average value in European Union countries with other macro values. Achieving fiscal sustainability as the macro component is also directly related to public deficits and economic growth trends, and public borrowing trends that directly affect public deficits in an economy focused on economic growth. The real value of these components not only directly impacts the existing economic growth but also creates an infrastructure that directly affects economic-fiscal sustainability with different values of the economy. The effect of public debt on economic growth in the European Union (EU) countries, besides being an average value, is significant with the scale effect of the values in EU countries as the dependent variable value of public deficits. In this context, revealing the deviations based on public values in public borrowings as a ratio of economic growth and economic growth, but also with other rates such as exchange rates, discounts, and inflation, has a meaningful place in the process of the interpretation of the sustainability of public deficits. In this respect, fiscal sustainability based on public borrowings in the EU necessitated its handling as the EU in general terms and the Euro Zone after 2017. This situation seems to be the reason for the continuation of public fiscal sustainability based on all countries, which is generally an average value in the EU, and a new borrowing policy subject to further economic growth and shaped by different strategies.